Respuesta :
For this case we have the following system of equations:
{y = 3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4
{y = 4x ^ 4 + 6x ^ 3-11
From here, we must match both equations.
By equating both equations, we obtain an equation that will depend on a single variable.
Matching we have:
3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4 = 4x ^ 4 + 6x ^ 3-11
Answer:
An equation that can be solved by using this system of equations is:
B.) 3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4 = 4x ^ 4 + 6x ^ 3-11
{y = 3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4
{y = 4x ^ 4 + 6x ^ 3-11
From here, we must match both equations.
By equating both equations, we obtain an equation that will depend on a single variable.
Matching we have:
3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4 = 4x ^ 4 + 6x ^ 3-11
Answer:
An equation that can be solved by using this system of equations is:
B.) 3x ^ 5-5x ^ 3 + 2x ^ 2-10x + 4 = 4x ^ 4 + 6x ^ 3-11
Answer:
(B) 3x^5-5x^3+2x^2-10x+4=4x^4+6x^3-11
Step-by-step explanation:
I took the edge test and got it right